Analisis Strategi Peningkatan Kinerja UMKM Makroni ER Melalui Digitalisasi Dengan Metode Data Envelopment Analysis (DEA) dan Quantitative Strategic Planning Matrix (QSPM) - Hilmi Aulawi; Rina Kurniawati; Nur Lela (Jurnal Kalibrasi, 2026)
The development of the digital economy offers significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to improve operational efficiency and competitiveness. However, not all MSME actors are able to utilize it optimally. This study aims to measure the operational efficiency of Makroni ER MSME and formulate digitalization-based priority strategies to enhance performance. The method used is Data Envelopment Analysis (DEA) with an input-oriented approach and the assumption of Constant Return to Scale (CRS) to evaluate the efficiency of 16 Decision Making Units (DMUs), along with the Quantitative Strategic Planning Matrix (QSPM) to formulate priority strategies. Based on the DEA results, 9 out of 16 DMUs were found to be efficient—namely in March, April, May, July, August, and September of the first year, as well as March and April of the second year. Meanwhile, the other 7 DMUs were declared inefficient—January, February, June, October, and December of the first year, as well as January of the second year—caused by excess inputs such as labor and working hours that were not proportional to output. Based on the QSPM results, the chosen priority strategy is data-driven production planning, as it achieved the highest TAS value. The objective is to improve operational efficiency, align production capacity with market demand, and reduce resource waste. This study demonstrates that the combination of DEA and QSPM provides an effective data-driven approach to improving MSME performance and operational efficiency in the digital era.